Complete genome sequence of Staphylococcus aureus, strain ILRI_Eymole1/1, isolated from a Kenyan dromedary camel - Zubair, Saima; Fischer, Anne; Liljander, Anne M.; Meens, Jochen; Hegerman, Jan; Gourlé, Hadrien; Bishop, Richard P.; Roebbelen, Ina; Younan, Mario; Mustafa, Mudassir Imran; Mushtaq, Mamoona; Bongcam-Rudloff, Erik; et al. (Springer, 2015)
We report the genome of a Staphylococcus aureus strain (ILRI_Eymole1/1) isolated from a nasal swab of a dromedary camel (Camelus dromedarius) in North Kenya. The complete genome sequence of this strain consists of a circular chromosome of 2,874,302 bp with a GC-content of 32.88 %. In silico annotation predicted 2755 protein-encoding genes and 76 non-coding genes. This isolate belongs to MLST sequence type 30 (ST30). Phylogenetic analysis based on a subset of 283 core genes revealed that it falls within the human clonal complex 30 (CC30) S. aureus isolate cluster but is genetically distinct. About 79 % of the protein encoding genes are part of the CC30 core genome (genes common to all CC30 S. aureus isolates), ~18 % were within the variable genome (shared among multiple but not all isolates) and ~ 3 % were found only in the genome of the camel isolate. Among the 85 isolate-specific genes, 79 were located within putative phages and pathogenicity islands. Protein encoding genes associated with bacterial adhesion, and secretory proteins that are essential components of the type VII secretion system were also identified. The complete genome sequence of S. aureus strain ILRI_Eymole1/1 has been deposited in the European Nucleotide Archive under the accession no LN626917.1.